Perancangan Video Dokumenter Rabab Pasisia Sebagai Upaya Pelestarian Seni Budaya Minangkabau - Dendi Nofendri; Melisa Suardi (Iam-Indonesia, 2024)
Abstract Abstract This final project is entitled Designing a Rabab Pasisia Documentary Video as an Effort to Preserve Minangkabau Cultural Arts in audio-visual form. The data used in this design are verbal data, visual data and data obtained through observation, interview documentation and internet sources which are analyzed using the SWOT theory. Through this research method, the results achieved are to see the response of the community when listening to rabab. So we can see opportunities to preserve rabab as Minangkabau culture. The design process that produces the main media in the form of documentary videos as a tool to invite and preserve rabab pasisia as Minangkabau culture. The supporting media which are the main attraction in efforts to preserve rabab pasisia such as: stickers, posters, totebags, t-shirts, xbanners. Keyword : Rabab, Documentary Video, Music, Tradition